Optimizing extrusion for maximum resistant starch: Unlocking the potential of banana flour - Kembabazi, Stellamaris; Mutambuka, Martin; Zawawi, Norhasnida; Mugampoza, Ediriisa; Shukri, Radhiah; Muranga, Florence Isabirye (Elsevier, 2025)
Banana starch, particularly rich in resistant starch type 2 (RS2), is known for its physiological benefits, but it lacks thermal stability compared to resistant starch type 3 (RS3). This study explored the use of twin-screw extrusion to modify native starch into the more thermally stable RS3 in banana flour derived from East African Highland cooking bananas. Using a central composite design, four variables; banana cultivar, feed moisture, barrel temperature, and screw speed were optimized. The highest RS content (38 %) was achieved under the following conditions: cultivar Enyeru, 18 % feed moisture, 90 °C barrel temperature, and 300 rpm screw speed. Post-cooking evaluation of the optimized extrudate showed significant RS retention and improved thermal stability. The increased RS positively impacted the functional properties: solubility, swelling power, water absorption capacity, and oil absorption capacity. Extrusion further improved the banana flour attributes with better paste stability against shear and heat, as well as reduced bulk density and tannin. These findings highlight the potential of extrusion technology to enhance the RS3 content in banana flour, offering new opportunities for functional food applications.